2014
DOI: 10.1098/rsbl.2014.0187
|View full text |Cite
|
Sign up to set email alerts
|

Maternally derived chemical defences are an effective deterrent against some predators of poison frog tadpoles ( Oophaga pumilio )

Abstract: Parents defend their young in many ways, including provisioning chemical defences. Recent work in a poison frog system offers the first example of an animal that provisions its young with alkaloids after hatching or birth rather than before. But it is not yet known whether maternally derived alkaloids are an effective defence against offspring predators. We identified the predators of Oophaga pumilio tadpoles and conducted laboratory and field choice tests to determine whether predators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…with its front legs, it immediately rejected the observation is consistent with previous experiments in which attacked and then rejected (Szelistowski 1985, Stynoski 2014, Murray 2016. It is likely that the spiders evaluate dendrobatid chemical cues received during contact and deem them unpalatable (Murray 2016; but see Summers 1999).…”
Section: B Asupporting
confidence: 76%
“…with its front legs, it immediately rejected the observation is consistent with previous experiments in which attacked and then rejected (Szelistowski 1985, Stynoski 2014, Murray 2016. It is likely that the spiders evaluate dendrobatid chemical cues received during contact and deem them unpalatable (Murray 2016; but see Summers 1999).…”
Section: B Asupporting
confidence: 76%
“…Alkaloid defenses of O. pumilio are also known to vary within populations (Daly et al 1994;Saporito et al 2010aSaporito et al , 2012Stynoski et al 2014aStynoski et al , 2014b, and in the current study, differences in alkaloid defenses and palatability were observed between sexes and life stages for one population. Assays with the ant, E. ruidum at La Selva, Costa Rica found differences in palatability that were largely attributed to differences in alkaloid quantity.…”
Section: Discussionsupporting
confidence: 55%
“…; Stynoski et al. ; Umbers and Mappes ). If color elements of larval and adult warning coloration are genetically correlated, variation expressed in adult coloration could be maintained not only via direct responses to selection on color traits in adults but also through indirect responses of selection on larval coloration and vice versa.…”
mentioning
confidence: 99%